Das bedingungslose Grundeinkommen: Eine (leider) nicht bezahlbare Idee - Florian Habmacher; Gebhard Kirchgässner (Center for Research in Economics, Management and the Arts (CREMA), 2016)
On July 5, this year, Swiss citizens will decide about the introduction of an unconditional basic income. It should amount to 2'500 CHF per mo nth for adults and 625 CHF for children. Total expenditure would be about 200 Billion CHF, a pa rt of which is alr eady covered by today s social security benefits. The proposed financia l concept is unrealisti c. The same holds, how- ever, for financing this system by the value added tax or the income tax. This once again shows that an unconditional basic income is either to o low to secure without additional income a decent existence or it cannot be financed if it is high enough to fulfil this objective. The same holds for the related concept of the negative income tax. Moreover, it is also very hard to justify a truly unconditional basic income for ethical reasons.
Additional information: Überarbeitete und ergänzte Fassung des CREMA Workingpapers 2013-08
Keywords: I38; 330; Unconditional Basic Income; Negative Income Tax